Synthesis, antimicrobial activity, structure-activity relationship and cytotoxic studies of a new series of functionalized (Z)-3-(2-oxo-2-substituted ethylidene)-3, 4-dihydro-2H-benzo[b][1, 4]oxazin-2-ones. Issue 18 (15th September 2017) - Sharma, Ritu; Yadav, Lalit; Lal, Jaggi; Jaiswal, Pradeep K.; Mathur, Manas; Swami, Ajit K.; Chaudhary, Sandeep
Graphical abstract: Abstract: A new series of functionalized ( Z )-3-(2-oxo-2-substituted ethylidene)-3, 4-dihydro-2 H -benzo[ b ][1, 4]oxazin-2-ones23 –26, incorporating pharmaceutically privileged substructures such as cyclopropyl, naphthyl, biphenyl and cyclohexylphenyl were synthesized in excellent yields. All the synthesized compounds were screened for their in vitro antibacterial activity against gram-(+)ve and gram-(−)ve bacterial species i.e. S. griseus, S. aureus, B. subtillis and E. coli as well as in vitro antifungal activity against fungal species i.e. F. oxysporium, A. niger, P. funiculosum and T. reesei, respectively. In this study, compounds containing c yclopropyl and cyclohexylphenyl substructures were identified as promising antimicrobial agents than standard drugs, ampicillin and chloramphenicol as well as ketoconazole. SAR study illustrates that electron-withdrawing groups increases the antibacterial as well as antifungal activity of 2-oxo-benzo[1, 4]oxazines and vice versa. Compounds23e and26e, the most active compounds of the series, displayed promising antibacterial activity than Ampicillin and Chloramphenicol. Moreover, compound26d showed promising antifungal potency as compared to Ketoconazole. Cytotoxic studies of the active compounds i.e.23c –e, 24e, 25d and26d –e found to be non-toxic in nature in 3T3 fibroblast cell lines using MTT assay.